The milkfish industry marketing channels in Iloilo Province trends and prospects - Candido, Rena E.; Seterra, Louie S.; Ramos, Imee Jane R.; Suson, Mariam P. (2002.)
Fish industry has been one of the developing industries in the country. However, alarming issues regarding indiscriminate fishing activities led to the declining condition of captured fishery products. Thus, aquaculture products played a vital role in making up for the shortages of fish supply. Aquaculture is widely practiced in the country, today. the most well-known cultured fish in the country in the milkfish, or bangus, its local name. This paper describes the marketing channels involved in the milkfish industry as well as its trends and prospects. This study is only limited to the Iloilo Province, and it also includes the attitudes of the key factors in the different marketing channels involved. As time progresses and economy changes, there are different activities involved in each marketing channel that includes restrictions and legal requirements, which are imposed to regulate the business. Backward and forward channels have also been part of the research. Backward channels involved the pathway taken by the milkfish from the fry catchers to the producers. Middlemen identified in the research included wholesaler, wholesaler-retailer, wholesaler-shipper, buyer-seller, buyer-seller, institutional buyers, and those middlemen involved in the backward an forward channel. forward channels involved the pathway taken by the milkfish from the retailers to the final consumers. Retailers included retailer-market vendors, retailer ambulant, and retailer consumer. Different factors attributed to the development of the marketing channels of milkfish in the province of Iloilo include government's role, competition, relationship among channels, efficient use of resources, supply and demand, growth, innovations and inventions. Milkfish industry will continue to develop as long as the supply and demand of milkfish will continue to increase taking into consideration the condition of the fish industry as a whole, in terms of profitability, stability, and relationship among key actors in the different marketing channels.
Research Paper (BA 200-Business Research). -- [Iloilo City] : University of the Philippines Visayas - College of Management, April 2002..